Maternal exposure to bis(2-ethylhexyl) phthalate during the thyroid hormone-dependent stage induces persistent emotional and cognitive impairment in middle-aged offspring mice. (May 2022) - Lv, Jia; Li, Yanling; Chen, Jianrong; Li, Rong; Bao, Chao; Ding, Zheng; Ren, Wenqiang; Du, Zhiping; Wang, Sheng; Huang, Yichao; Wang, Qu-nan
Abstract: Prenatal DEHP exposure can cause offspring neurodevelopmental toxicity, but the persistent effects of such exposure window are unclear. This study aimed to investigate the lasting neurobehavioral impact of DEHP on offspring following early exposure from GD9.5 (fetal neural tube closure) to GD16.5 (fetal thyroxin, TH, synthesis). Data showed maternal exposure to DEHP during the thyroid hormone-dependent stage induced a range of neurobehavioral phenotypic changes in adult and middle-aged mice, including anxiety, depression and cognitive impairment. Significant reductions in free TH, TH transporters, and TH metabolic enzyme deiodinase II (D2) were observed in the fetal brain, whereas D3 was elevated, indicating that TH signaling disruption was caused by in utero exposure. Gene expression analyses suggested the expression levels of the TH receptors Trα1, Trβ1 and their downstream target, brain-derived neurotrophic factor, were significantly attenuated, which may partially explain the mechanisms of neurodevelopmental impairment. This study provides new evidence of the persistent effects of sex-specific neurodevelopmental impairment due to in utero DEHP exposure, possibly through damage to the fetal brain TH signaling systems that causes lifelong brain damage. These results further suggest a profound neurobehavioral toxicity of DEHP that may be programmed during early developmental stage exposure and manifested later in life. Graphical abstract: Image 1 Highlights: Maternal TH-dependent DEHP exposure induced lasting neurological damage in mice. Persistent emotional & cognitive phenotypes were sex-dependent in the offspring. Perturbations in fetal brain TH signaling systems may underlie middle-age damage.